A model for the dispersion of puffs into the planetary boundary-layer. (1st January 2000) - Rizza, U.; Mangia, C.; Degrazia, G.A.; Tirabassi, T.
A model for the dispersion of Gaussian puffs into the planetary boundary-layer is presented. The model relies on the relative diffusion theory in which the rate of expansion of the puff is expressed in terms of the spectral properties of turbulence. A new spectral formulation for the turbulent velocities is used, which is valid for different stability conditions ranging from stable to convective. As a preliminary model evaluation, a continuous plume from the experimental campaign of Copenhagen is reproduced as a superposition of discrete emitted puffs. Comparison between predicted and measured ground level concentration data shows a good agreement both for crosswind integrated concentrations and arcwise maxima.